The effect of disulfidptosis induced by glucose starvation in SLC7A11high ovarian cancer cells - Chen, Yating; Ou, Yu-Hua; Shi, Wenjing (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveDisulfidptosis is a glucose deprivation-induced cell death mechanism driven by disulfide stress-mediated actin cytoskeleton disintegration. This study explored whether SLC7A11high ovarian cancer (OC) undergoes disulfidptosis under conditions of glucose starvation. This study aimed to provide a new treatment option for OC.MethodsInitially, we carried out an assay to assess the cell viability of IOSE 80 and OVCAR 3 cells under conditions of glucose sufficiency and starvation. Subsequently, we examined the difference in SLC7A11 expression between the two cell types under the specified conditions. The intracellular NADP+/nicotinamide adenine dinucleotide phosphate (NADPH) ratio and the oxidized glutathione disulfide/reduced glutathione (GSSG/GSH) ratio were quantified using the test kit. In addition, the effect of SLC7A11 on cell death was studied using SLC7A11 transporter activity inhibitors. Cell Counting Kit-8 (CCK-8) was used to investigate the effect of intracellular disulfide bond levels on cell death due to glucose starvation. Finally, we investigated the effect of reactive oxygen species (ROS) on cell death.ResultsThe results revealed that the SLC7A11 expression level in OVCAR 3 cells was higher than that in IOSE 80 cells, and OVCAR 3 cells exhibited a lower tolerance to glucose starvation. Glucose starvation stimulates SLC7A11 expression in OVCAR 3 cells, and SLC7A11 facilitates cell death in OC cells under conditions of glucose starvation. Elevated disulfide bond levels in ovarian cancer cells promote cell death under glucose starvation conditions.ConclusionGlucose starvation induces high SLC7A11 expression in OC cells, resulting in cell death. This type of cell death is associated with NADPH depletion in the cell and the accumulation of disulfides. Therefore, it is considered that disulfidptosis may occur in SLC7A11high OC cells under glucose starvation conditions.